Membangun Budaya Religius Di Sekolah: Suatu Kajian Terhadap Konsep, Pola, Model, Pendekatan, Metode, Strategi Dan Problematika - Sutarto Sutarto (Jurnal Pendidikan dan Konseling (JPDK), 2022)
Religious culture needs to be developed in schools. However, not all schools can build a religious culture to the fullest. This research library research aims to describe the concepts, patterns, models, approaches, methods, strategies, and problems encountered in schools in building a religious culture. Research data comes from books, scientific articles, and research results on the topics discussed. Data collection techniques were carried out by searching, reading, quoting, analyzing, and interpreting data from the literature, then analyzing by descriptive and comparative analysis and checking the data's validity by source triangulation and theoretical triangulation. The results showed that building a religious culture in schools can be done with various patterns, models, approaches, methods, and strategies according to the characteristics of students. For the religious culture built in schools to run effectively, several things must be done, namely determining religious values ??to be cultivated, making joint commitments, socializing, and cultivating religious values ??in daily behavior attitudes.